Aerodynamic Drag Analysis of Superpressure and Zero Pressure Balloons using Large Eddy Simulations (LES) - B. Lohani; C. Mascarenhas (Journal of Applied Fluid Mechanics, 2025)
Stratospheric balloons are an essential part of the scientific research community. In previous stratospheric balloon models used for trajectory prediction and station-keeping, the aerodynamic drag has usually been modeled as similar to that of a sphere. However, with recent proposals to use propulsion systems on the payload of stratospheric balloons to achieve trajectory control in the horizontal plane, it is important to refine our understanding of the drag of stratospheric balloons, especially at low horizontal velocities near transition, where spherical assumptions may deviate significantly. This study conducts a Computational Fluid Dynamics (CFD) investigation into the aerodynamic characteristics of both superpressure balloons (SPBs) and zero pressure balloons (ZPBs) using Large Eddy Simulations (LES). The analysis was conducted over a range of Reynolds numbers that correspond to reasonable forward airspeeds for horizontal stratospheric propulsion-based balloon systems. The results show that both balloons have drag characteristics qualitatively similar to a sphere. This includes an initially high drag coefficient, a drag crisis, and a lower eventual drag coefficient. Quantitatively, however, differences emerge between the balloon aerodynamics and that of a sphere. For example, the drag crisis occurs at a lower Reynolds number for both types of balloons when compared to a sphere. This is critical as proposed propulsion-based balloon systems aim to operate near the Reynolds number where this drag crisis occurs. The drag coefficient for the SPB was found to be less than the ZPB at all Reynolds numbers. A sensitivity analysis revealed that increasing the number of gores decreased the drag coefficient, with the flow separation delayed and the wake narrowing as the gore count increased. For example, a reduction of 32% in drag was observed when the number of gores increased from 30 to 50.